2008
DOI: 10.1002/hep.22184
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of hepatitis C virus RNA from the peripheral blood mononuclear cells of blood donors who spontaneously or therapeutically control their plasma viremia

Abstract: We determined whether hepatitis C virus (HCV) RNA could be detected associated with peripheral blood mononuclear cells (PBMC) of seropositive blood donors who had spontaneously or therapeutically cleared their plasma viremia. Blood donor plasma viremia status was first determined with a highly sensitive transcription-mediated amplification (TMA) test performed in duplicate assays. PBMC from 69 aviremic and 56 viremic blood donors were then analyzed for the presence of HCV RNA with TMA adapted to detect viral R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
3

Year Published

2008
2008
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 45 publications
2
71
3
Order By: Relevance
“…7 This latest observation was confirmed by another recent study with a complete clearance of HCV RNA from the PBMCs of blood donors who spontaneously or therapeutically control their plasma viremia. 8 In conclusion, the excellent review performed by Welker and Zeuzem on occult HCV infection confirm our data and those of two other studies using sensitive assays and liver/PBMC assessment, and reinforce the absence of evidence of occult HCV infection. …”
Section: The Myth Of Occult Hepatitis C Infectionsupporting
confidence: 89%
“…7 This latest observation was confirmed by another recent study with a complete clearance of HCV RNA from the PBMCs of blood donors who spontaneously or therapeutically control their plasma viremia. 8 In conclusion, the excellent review performed by Welker and Zeuzem on occult HCV infection confirm our data and those of two other studies using sensitive assays and liver/PBMC assessment, and reinforce the absence of evidence of occult HCV infection. …”
Section: The Myth Of Occult Hepatitis C Infectionsupporting
confidence: 89%
“…Forty-six controllers were followed for a median of 16 months; 39% were female and 37% were African-American (Table 1). The median self-reported duration of HIV diagnosis at study entry was 13 years, and the median baseline CD4 ϩ T-cell count was 753 cells/mm 3 . As a comparison group, we measured plasma HIV RNA levels in 37 long-term HAART-treated subjects who had undetectable plasma levels (when using conventional assays) for at least 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…As a comparison group, we measured plasma HIV RNA levels in 37 long-term HAART-treated subjects who had undetectable plasma levels (when using conventional assays) for at least 5 years. The median duration of viral load suppression was 7 years (interquartile range [IQR], 6 to 7 years), and the median baseline CD4 ϩ T-cell count was 485 cells/mm 3 . The self-reported CD4 nadir of this group was 85 (IQR, 37 to 172).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of HCV RNA in plasma samples from 70%-75% of blood donors with indeterminate immunoblot results has also been reported by other groups in Brazil (6,7); however, in contrast, other investigators have reported RNA prevalence in such samples to be ≈2.5% (1,8). Indeterminate RIBA test results can indicate seroconversion or seroreversion or, occasionally, a chronic infection when RNA HCV is detected in plasma (9,10). To provide better understanding of the meaning of these indeterminate results, ongoing follow-up studies are examining the immune status of these persons.…”
Section: Hepatitis C Virus In Blood Donors Brazilmentioning
confidence: 99%